PENGARUH VISKOSITAS BBM, JARAK DAN KECEPATAN PEMOMPAAN TERHADAP PERFORMA TEKANAN HIDROLIK INJEKTOR MESIN DIESEL - Joko Yunianto Prihatin; Irvan Saputra Al Amin Amin; Slamet Pambudi; Karminto Karminto (Teknika, 2023)
ABSTRACT Euro-4 emission standards for motor vehicles or those implementing a fuel injection system. The quality of the injector can only be determined with a Nozzle tester. The main problem is that the pressure data from the test results on the nozzle tester before and after the service is used as a reference for the suitability of the fuel misting quality in the engine manual. The aim of this research is to determine the minimum and maximum pressure performance of diesel injectors. The method applied is to provide variations in fuel type, pumping distance and pumping interval on the nozzle tester with the OA L4 experimental design. The results achieved are that the maximum working pressure value on the jack nozzle tester is 145kg/cm2 and the minimum is 126.6kg/cm2. 1st composition with variations in diesel fuel viscosity, full distance 24cm, lever pressing speed 10 times/sc which produces maximum working pressure. And the minimum pressure is at the 4th composition with variations in dexlite fuel viscosity, full distance 12cm, lever pressing speed 15 times/sc. Keywords: injector, fuel, pumping, nozzle tester